Hakikat Kurikulum dalam Perspektif Filsafat Pendidikan Islam - Ananta Pramayshela; Erma Yanti Tanjung; Laila Qadaria (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
To achieve the goals of religious education (Islamic education), a curriculum is needed that is in accordance with the goals of Islamic education, age level, development of child psychologists and student skills. In this case the author uses a qualitative research method, which leads to literature study, literature study. Manhaj as a clear path that is passed by educators or training teachers with the people they train to develop their knowledge, skills, and attitudes as well as values, developing a curriculum, must be in accordance with things that can realize the educational goals that have been set. The scope of Islamic education includes everything related to Islamic education,